2018
DOI: 10.1111/nph.15398
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic activation of cortical cell division during the accommodation of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizas (AMs) between plants and soil fungi are widespread symbioses with a major role in soil nutrient uptake. In this study we investigated the induction of root cortical cell division during AM colonization by combining morphometric and gene expression analyses with promoter activation and protein localization studies of the cell-plate-associated exocytic marker TPLATE. Our results show that TPLATE promoter is activated in colonized cells of the root cortex where we also observed the appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…ROC lines, already available in the laboratory (Chabaud et al, 2011;Genre et al, 2013), expressed a nuclear localized cameleon YC2.1 construct, and were propagated on M medium (B ecard & Fortin, 1988) at 25°C in the dark, in vertically oriented petri dishes to favor a regular fishbone-shaped root system (Chabaud et al, 2002). Explants with consistent morphology and an identical number of lateral roots were chosen for all ROC-based experiments (Russo et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…ROC lines, already available in the laboratory (Chabaud et al, 2011;Genre et al, 2013), expressed a nuclear localized cameleon YC2.1 construct, and were propagated on M medium (B ecard & Fortin, 1988) at 25°C in the dark, in vertically oriented petri dishes to favor a regular fishbone-shaped root system (Chabaud et al, 2002). Explants with consistent morphology and an identical number of lateral roots were chosen for all ROC-based experiments (Russo et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Root-nodule symbiosis has evolved by co-opting signaling mechanisms from the more ancient arbuscular mycorrhizal symbiosis between plants and nutrientdelivering fungi of the glomeromycotina [13,14]. It was recently reported that attachment of the fungus to the root surface induces cell division in the cortex [15], similar to the initial cell-division events observed during rhizobial infection and nodulation. Furthermore, priming of cells that neighbor colonized cells has been observed [12,16].…”
Section: Current Biologymentioning
confidence: 99%
“…However, it was recently suggested that cell-division-related processes also occur in cortical cells during the accommodation of AM fungi (Russo et al, 2019).…”
Section: " "mentioning
confidence: 99%